Can bilateralism ease the pains of multilateral trade liberalization? - Olivier Cadot; Jaime de Melo; Marcelo Olarreaga (World Trade Organization (WTO), 1998)
Using the influence-driven approach to endogenous trade-policy determination, we show how a free-trade agreement (FTA) with rules of origin can work as a device to compensate losers from trade liberalization. The FTA constructed in this paper is characterized by external tariff structures that are negatively correlated across member countries, ensuring efficiency gains and, through reduced average protection, compatibility with the multilateral trading system's requirements. It is also politically viable, and we demonstrate that, in the countries concerned, governments are willing to include its formation in the political agenda in spite of the fact that, in equilibrium, political contributions from producer lobbies decline after the agreement.
Keywords: F13; F13; F15; 330; Free-trade areas; political economy